Characterization, In Vitro Biological Activity and In Vivo Cardioprotective Properties of Trametes versicolor (L.:Fr.) Quél. Heteropolysaccharides in a Rat Model of Metabolic Syndrome - Marina Nikolic; Nevena Lazarevic; Jovana Novakovic; Nevena Jeremic; Vladimir Jakovljevic; Vladimir Zivkovic; Jovana Bradic; Danijela Pecarski; Gülsen Tel-Çayan; Jasmina Glamocija; Marina Sokovic; Andrej Gregori; et al. (MDPI AG, 2023)
The present study aimed to examine the biological activity and cardioprotective potential of Trametes versicolor heteropolysaccharides (TVH) in a rat model of metabolic syndrome (MetS). This study included 40 Wistar rats divided into 5 groups: CTRL-healthy non-treated rats; MetS-non-treated rats; and H-TV, M-TV and L-TV-rats with MetS treated with either 300, 200 or 100 mg/kg TVH per os for 4 weeks. After finishing the treatment, we conducted an oral glucose tolerance test (OGTT), hemodynamic measurements and the animals were sacrificed, hearts isolated and subjected to the Langendorff technique. Blood samples were used for the determination of oxidative stress parameters, lipid status and insulin levels. We showed that α-amylase inhibition was not the mode of TVH antidiabetic action, while TVH showed a moderate inhibition of pathogenic microorganisms' growth (MIC 8.00 mg·mL−1; MBC/MFC 16.00 mg·mL−1). H-TV and M-TV significantly reduced the level of prooxidants (O2−, H2O2, TBARS; p < 0.05), increased antioxidants activity (SOD, CAT, GSH; p < 0.05), reduced blood pressure (p < 0.05), improved glucose homeostasis in the OGTT test (p < 0.05), and ejection fraction (p < 0.05) and cardiac contractility (p < 0.05) compared to MetS (p < 0.05). Moreover, TVH treatment normalized the lipid status and decreased insulin levels compared to MetS rats (p < 0.05). The obtained results demonstrated that the TVH may be considered a useful agent for cardioprotection in MetS conditions.